Awareness, Interest, and Desire: A Comparative Analysis of Modern and Traditional Advertisement to Influence Consumer Buying Behavior - Askaree, Mansoor Waqas; Arif, Abdur Rehman; Durrani, Shahzada Muhammad Emaad Khan (Pakistan Journal of Humanities and Social Sciences, 2023)
Advertising is the most common means of communicating with consumers and a method for gaining their attention. This study is founded on a comparison of the awareness, interest, desire, and decision-making characteristics of digital and traditional advertising. This research was carried out in Shaheed Benazirabad. Exact sample size was 250 and responses were collected via a self-administered questionnaire. The T-test and ANOVA were utilized to analyze the data. Significant variations and disparities among variables and enormous market effects are revealed by the findings. As the variables are significant to one another and the result demonstrates a positive relationship, it may be useful for future research and for informing marketing strategies and promotional techniques.